Effect of Dose and Type of Liquid Organic Fertilizer on Early Growth of Cocoa Seedlings (Theobroma Cacao L.) - Muhammad Faisal Gunawan; Gatot Subroto; Dyah Ayu Savitri; Oria Alit Farisi (Protech Biosystems Journal, 2023)
The purpose of this research was to determine the effect of dose and type of liquid organic fertilizer as well as the interaction between dose and type of liquid organic fertilizer on the early growth of cocoa seedlings. This study used various kinds of POC namely GDM, NASA, Hantu and Guano. To support the success of POC application, different doses were also used in the treatment. The research was conducted in the greenhouse of Patrang Sub-district, Patrang District, Jember Regency in 2023. This study used a complete randomized design (CRD) with 2 factors. The first factor is the dose consisting of 3 levels, namely D1 (10ml/plant), D2 (15ml/plant) and D3 (20ml/plant). The second factor is the type of liquid organic fertilizer consisting of 4 levels, namely P1 (GDM), P2 (NASA), P3 (Superior plant hormone (Hantu)) and P4 (Guano). The results showed there was no interaction between dose and various kinds of liquid organic fertilizers. The application of dose affected the wet weight of plants and leaf area. Various kinds of liquid organic fertilizers affected the number of branches of cocoa seedlings.